AB0346 The combined inflammatory arthritis questionnaire for assessment of functional disability and quality of life: Assessment of the minimal clinically important difference and real clinically important difference in patients with rheumatoid arthritis. (23rd January 2014) - El Miedany, Y.; El Gaafary, M.; Youssef, S.; Palmer, D.
Abstract : Objectives: 1. To estimate the Minimal Clinically Important Differences (MCID) as well as the Real Clinically Important Difference (RCID) of the Combined Inflammatory Arthritis Questionnaire for functional disability and Quality of life for worsening and improvement that were experienced in RA patients. Methods: 547 RA patients starting their DMARDs therapy completed a PROMs questionnaire at 0 and 6 months of therapy. The questionnaire includes assessments for functional disability (CIAQ-Fn), quality of life (CIAQ-QoL), VAS for parameters of disease activity: pain, patient global assessment, and self-helplessness. DAS-28 was calculated to assess disease activity. Scores of change at baseline and 6 months of therapy for each of the disease activity parameters were used as external standards as follows: ([final score-baseline score]/baseline score × 100). Four categories of change were derived. 1. patients with no change or a worsening in their scores, 2. improvement of <20%, 3. improvement of <50%, 4. improvement >50%. Categories of change for DAS-28 were as follows: 1. Patients with no change (<0.6) or worsening of DAS score, 2. 0.6-1.2 change of DAS score, 3. >1.2 change of DAS score, 4. >1.9 of DAS score. Changes in the CIAQ-Fn and -QoL scores were estimated for each patient by subtracting baseline scores from 6-months follow-up scores. MCID was determined by estimating the mean changes in CIAQ-Fn and -QoL scores in patients who showed 1 level of improvement on the disease activity parameters. Three categories of change were identified: 1. percentage of patients whose follow-up score did not change (% same), 2. % of patients whose follow-up score improved (% better), and 3. % of patients whose follow-up scores declined (% worse). RCID was determined by estimating the mean changes in CIAQ-Fn and -QoL scores in patients who showed 2 levels of improvement on the disease activity parameters. Results: Depending on the external standards used, the MCID for improvement of the CIAQ-Fn was -0.20, while the MCID for worsening was +0.22; whereas the MCID for improvement of the CIAQ-QoL was -0.21, and the MCID for worsening was +0.22. RCID for improvement of the CIAQ-Fn was -0.52 and for CIAQ-QoL was -0.56. MANOVA results linking score changes of both CIAQ-Fn and CIAQ-QoL to changes in RA severity were statistically significant. Differences in categorical changes among both scores were also significant across the levels of change in the disease activity parameters. Logistic regression analysis revealed significant differences in categorical changes (% better, %same, % worse) of both CIAQ-Fn and -QoL scores across the groups that differed in the level of change in RA severity. Conclusions: Both CIAQ-Fn and –QoL are responsive to change. The MCID of both scores for improvement as well as worsening were sensitive to important short term changes in RA patients. RCID values are 2 to 3 times greater than MCID values. This range of MICD and RICD changes will help investigators interpret changes in CIAQ-Fn and –QoL scores in clinical trials involving RA patients, both at the group level (average change) and individual patient level (categorical change). Disclosure of Interest: None Declared